2022
DOI: 10.3389/fnut.2022.895192
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dietary Supplement for Skin Moisturizing in Healthy Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundThe dietary supplement industry offers many oral cosmetics that purportedly assist in skin moisturization often with unclear evidence supporting efficacy and safety. To update the accessible proofs pertaining to the safety and effectiveness of oral dietary supplements to facilitate skin moisturizing via an all-around review and meta-analysis.MethodsThree on-line databases [Pubmed, Embase, and Cochrane Library (CENTRAL)] were retrieved from January 2000 to November 2021. An overall 66 randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 98 publications
0
10
0
2
Order By: Relevance
“…In addition, our results are supported by the fact that the topical application of 4% genistein has been shown to increase skin thickness and blood vessels [ 26 ], the concentration of hyaluronic acid, glycosaminoglycan, and fibroblasts in the dermis [ 27 ], as well as the amount of type I and type III facial collagen [ 17 ], all of which are factors leading to a reduction in skin wrinkles. Moreover, apart from genistein, the GEN product contained some other active substances, including vitamin E [ 12 , 28 ], vitamin B3 [ 19 , 29 ], and ceramide [ 20 , 30 ], all of which have evidence indicating their anti-wrinkle properties [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results are supported by the fact that the topical application of 4% genistein has been shown to increase skin thickness and blood vessels [ 26 ], the concentration of hyaluronic acid, glycosaminoglycan, and fibroblasts in the dermis [ 27 ], as well as the amount of type I and type III facial collagen [ 17 ], all of which are factors leading to a reduction in skin wrinkles. Moreover, apart from genistein, the GEN product contained some other active substances, including vitamin E [ 12 , 28 ], vitamin B3 [ 19 , 29 ], and ceramide [ 20 , 30 ], all of which have evidence indicating their anti-wrinkle properties [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ceramides, which are sphingolipids presenting in the intercellular space of the stratum corneum, play an essential role in structuring and maintaining the barrier property of the epidermis and exhibit a certain level of efficacy in improving skin dryness [ 15 , 16 ]. Although there are several in vitro and in vivo studies on the benefits of genistein [ 17 ], vitamin E [ 18 ], vitamin B3 [ 19 ], and ceramide [ 20 ] alone, limited studies have been conducted to assess the effects of their combined regimen on facial skin.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in outcome after the trial intervention was calculated as the difference between the baseline and endpoint values. Since the included studies did not report the baseline-final correlation coefficient (Corr), we chose the commonly utilized value of 0.5 as the Corr value ( 26 , 27 ). We performed a meta-analysis when at least four studies included the same outcome measure and showed 95% CIs for statistical results, with P < 0.05 representing statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al reported that the concentration of moisture in the skin of mice treated with collagen peptides (CPs) was significantly higher compared with that of the control mice (p < 0.05) [55]. Sun et al revealed that collagen as a single supplement showed remarkable effects on skin hydration, with an SMD of 0.77 (95% CI 0.60, 0.94; p < 0.00001) compared with a placebo [56].…”
Section: Hydrationmentioning
confidence: 99%